Antiangiogenesis Activity Study of Awar-Awar Leaf Ethanolic Extract (Ficus Septica Burm. F.) By Chick Chorioallantoic Membrane Method - Lailiana Garna Nurhidayati; Agung Endro Nugroho; Bambang Retnoaji; Sudarsono Sudarsono; Nanang Fakhrudin (Universitas Gadjah Mada, 2021)
Cancer is one of the biggest causes of death after cardiovascular disease. Furthermore, alkaloid content of awar-awar leaf extract (Ficus septica Burm. f.) is reported to exhibit cytotoxic activity in several cancer cells. This research aims to identify the antiangiogenesis activity and potential of awar-awar leaf extract (Ficus septica Burm. f.) on chorioallantoic membrane (CAM) of chicken embryo inducted with basic fibroblast growth factor (bFGF). Awar-awar leaf extract was obtained by the maceration method by using ethanol 70%. CAM was cultured in ex ovo and then angiogenesis induced by bFGF and treated by using the concentrated extract of 0.013; 0.00975; 0.0065; and 0.00325 mg/mL. From now on, the observation was done macroscopically and microscopically. Macroscopic observation result shows that an inhibition occurred at the concentration extract of 0.013 mg/mL or equal to 62.30%, 0.00975 mg/mL or equal to 51.37%, 0.0065 mg/mL or equal to 28.42%, and 0.00325 mg/mL or equal to 13.11%. Meanwhile, the microscopic observation result shows that the higher concentration of the extract, the growth of new blood vessels is decreased, demonstrated by the reduced erythrocyte density, parallel blood vessel pattern, and looser cellular density mesenchymal tissue. Moreover, the statistical analysis result shows that the increasing concentration of extract could increase the inhibition of new blood vessel growth (p <0.05). So, awar-awar leaf ethanol extract can be used as an antiangiogenesis agent in CAM of chicken embryo induced with bFGF by ex ovo.